1992
DOI: 10.1111/j.1365-2184.1992.tb01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogonial apoptosis has three morphologically recognizable phases and shows no circadian rhythm during normal spermatogenesis in the rat

Abstract: In this study we examined the possibility that regular or circadian fluctuations occur in the frequency of spontaneous spermatogonial apoptosis. Apoptosis of A2, A3 and A4 type spermatogonia occurring spontaneously in the normal rat testis was studied by light and electron microscopy. Normal and apoptotic A3 spermatogonia were quantified in 36 animals killed at two-hourly intervals over a 24 h period. Three sequential phases of spermatogonial apoptosis were defined and quantified separately: (i) an early phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
122
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(135 citation statements)
references
References 18 publications
10
122
0
3
Order By: Relevance
“…Germ cell deletion during normal spermatogenesis has been estimated to result in the loss of up to 75% of the potential numbers of mature sperm cells in the adult testis (De Rooij et al, 1987;Huckins, 1978;Oakland, 1956). Detailed analyses of germ cell degeneration have been published (Allan et al, 1992;Clermont, 1962;De Rooij and Lok, 1987;Huckins, 1978;Kerr, 1992;Wing and Christiansen, 1982); morphometric analyses of semithin sections of perfusion-fixed testes have indicated that the loss of germ cells in the rodent testis is greatest during the mitoses of type A2, A3, and A4 spermatogonia and during the first meiotic division ( Figure 4). No degeneration occurs in type A1 spermatogonia, or in intermediate or type B spermatogonia (Johnson et al, 1984;Kerr, 1992) (Figure 4).…”
Section: Germ Cell Degeneration and Apoptosis During Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Germ cell deletion during normal spermatogenesis has been estimated to result in the loss of up to 75% of the potential numbers of mature sperm cells in the adult testis (De Rooij et al, 1987;Huckins, 1978;Oakland, 1956). Detailed analyses of germ cell degeneration have been published (Allan et al, 1992;Clermont, 1962;De Rooij and Lok, 1987;Huckins, 1978;Kerr, 1992;Wing and Christiansen, 1982); morphometric analyses of semithin sections of perfusion-fixed testes have indicated that the loss of germ cells in the rodent testis is greatest during the mitoses of type A2, A3, and A4 spermatogonia and during the first meiotic division ( Figure 4). No degeneration occurs in type A1 spermatogonia, or in intermediate or type B spermatogonia (Johnson et al, 1984;Kerr, 1992) (Figure 4).…”
Section: Germ Cell Degeneration and Apoptosis During Spermatogenesismentioning
confidence: 99%
“…On the basis of morphological evidence, it was first suggested that cell death of spermatogonia during normal spermatogenesis takes place through the apoptotic mechanism, the spermatocytes and spermatids, in contrast undergoing necrosis (Allan et al, 1992). Recently, however, quantification of small molecular weight DNA fragments and in situ DNA 3'end-labeling analyses of apoptosis in the testis have shown that spermatocytes and spermatids can also undergo apoptosis (Billig et al, 1995 Figure 5 Testosterone-mediated inhibition of apoptosis induced in human seminiferous tubules cultured in serum-free conditions.…”
Section: Germ Cell Degeneration and Apoptosis During Spermatogenesismentioning
confidence: 99%
“…The mechanisms of diabetes-related apoptosis are unclear. However, current studies have indicated that diabetes-mediated oxidative stres can induce apoptosis (Allan et al, 1992;Reiter et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of germ cells are present in the testes, while Sertoli cell support is finite. Thus, apoptosis is a normal and necessary occurrence during spermatogenesis, in order to select germ cells and regulate the number of germ cells [21][22][23][24][25][26]. In some cases, apoptosis may initiate but abort, in a process known as abortive apoptosis, leading to the ejaculation of mature sperm with apoptotic traits, such as fragmented DNA and membrane-bound Fas [27,28].…”
Section: Introductionmentioning
confidence: 99%